Simplications in the synthesis of short oligonucleotide blocks. - Broka, C (1980)
A rapid and convenient procedure has been developed for the synthesis of fully protected mono, di and trideoxyribonucleotides utilizing an aryl phosphoroditriazolide. It affords advantages over coupling strategies employing condensing reagents, such as 2,4,6-triisopropylbenzenesulfonyl tetrazolide in preparing small oligonucleotides and is relatively free of the drawbacks inherent in other approaches using bifunctional phosphorylating reagents. In particular, the synthesis of trinucleotide blocks without purification at the dimer stage is described.